Aspirational taste regime: Masculinities and consumption in pick-up artist training in China. (February 2023) - Liu, Haiping
Based upon 2 years of ethnographic fieldwork, this study proposes "aspirational taste regime" as a critical concept through which to examine the emergence of a discursively constructed normative system in China's Pick-Up Artist (PUA) training programs. By unpacking how taste is practiced both digitally and corporeally in these programs, the paper argues that Chinese PUA learners carefully curate taste for an illusionary, at times even deceptive, presentation of idealized masculinities to increase their matrimonial chances. In doing so, this paper extends the literature on taste regimes by moving beyond its typically Western focus. It directs attention to an aspirational taste regime that capitalizes on young men's aspirations for idealized masculinities and prescribes a seemingly effortless but in fact highly curated online presentation of cultural-capital-oriented consumption.